Judahite Gath in the Eighth Century B.C.E.: Finds in Area F from the Earthquake to the Assyrians - Chadwick, Jeffrey R. (Near Eastern archaeology, 2018)
After Philistine Gath fell to the Arameans in the late ninth century B.C.E. (Maeir 2008; 2012: 47–48) the huge city atop Tell eṣ-Ṣâfi/Gath was a ghost town for several decades. Some structures had been burnt or otherwise destroyed, but many were simply abandoned to the elements. As years passed, winter storms and the processes of nature eroded the roofs and walls of hundreds of ownerless houses and other buildings. The devastation was alluded to by the Judahite prophet Amos when he predicted the eventual demise of Samaria: “Go down to Gath of the Philistines,” he challenged the Israelites, to behold what complete desolation is like (Amost 6:2; Maeir 2004). Aside from the presence of a few squatters who settled in the north lower-city ruins near the Elah riverbed, the forlorn ghost town of Gath slowly decayed away, until a cataclysmic earthquake shook the entire region somewhere around 760 B.C.E. (Chadwick and Maeir, forthcoming; Maeir 2012:49–50).